Antithrombotic therapy recommendations in the European Society of Cardiology Guidelines : how robust are the randomized controlled trials underpinning them? - Santos, Catarina M. (2021)
© 2021. The Author(s). This is an open access article published by Thieme under the terms of the Creative Commons Attribution License, permitting unrestricted use, distribution, and reproduction so long as the original work is properly cited. (https://creativecommons.org/licenses/by/4.0/). Georg Thieme Verlag KG